VIBRATION TILLAGE. ANALYSIS OF TECHNOLOGIES AND APPLICATION PROSPECTS - POLISHCHUK, OLEKSANDR; ZAHNITKO, YAROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article analyzes the current state of research on vibratory tillage methods as a promising area for improving agricultural technologies. The problems of traditional tillage methods, in particular plowing, moldboardless, rotary, minimum and zero tillage, which, despite their widespread use, have significant limitations and disadvantages, are highlighted. The relevance of finding innovative approaches in view of the challenges associated with climate change, soil degradation, and the need for more efficient use of resources is substantiated. The principles of functioning of vibration tillage systems, which are based on the application of oscillatory motion to the working bodies of tillage tools, are considered. The mechanism of vibration action on the soil is analyzed, which consists in a temporary decrease in soil resistance due to a decrease in shear strength and friction between particles. The potential benefits of vibration tillage are highlighted, including: reduced energy costs, improved physical properties of the soil, increased weed control efficiency, better soil crushing, and the ability to work in different conditions. The article presents a comparative analysis of traditional tillage methods with vibration technologies in terms of energy consumption, impact on soil structure, weed control efficiency, equipment complexity, and other indicators. The available experimental models of vibration equipment are described, including plows with unbalancing devices, electromagnetic exciters, hydraulic vibrators, and structures with forced vibration excitation. The main limitations of vibration tillage technologies associated with the experimental status of most developments are identified, and the directions of further research are outlined, which should focus on optimizing vibration parameters for different soil types, developing cost-effective equipment, and conducting field tests in different agroclimatic zones. It is concluded that vibration tillage has a significant potential for the development of more sustainable and efficient farming systems.
Keywords: vibrations; vibration exciter; energy consumption; plow; soil; research